Rethinking monetary theory in light of Keynes and the crisis - Lavoie, Marc (Brazilian Keynesian Review, 2017)
The purpose of the present paper is to examine the main changes that have occurred or that need to occur in monetary economics, and to do this in light of what Keynes told us 80 years ago in his General Theory, or even more than 85 years ago when he wrote the Treatise on Money.  Inflation targeting and central bank independence are re-examined, as are the standard views of the money multiplier and of the fractional-reserve system. Unconventional monetary policies, although previously suggested by Keynes, appear to be a disguised return to Monetarism and the actual impact of quantitative easing must be understood in light of a theory of endogenous money with monetary implementation occurring within a framework where the target interest rate is set at the floor of the corridor.